Oligarchy of Power in The Management of C-Mine Resources in Noemuti, North Central Timor Regency - S.D. Dari, Alfridus; Frans B.R. Humau; Syahrin B. Kamahi; Maria M. Niis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This paper raises the dynamics of oligarchic power relations in the management of C-quarry mining resources in the form of stone in Noemuti District, North Central Timor Regency. This research uses the oligarchy theory of Jeffrey Winters as a basis for analysis in looking at mining problems that seem to be deadlocked when dealing with power authorities in resource management in the regions. The practice of oligarchy in Winters' theory uses 5 main approaches. But in this paper, it only limits to two approaches, namely the concentration of wealth and the concentration of power. Facing the dynamics of oligarchy that strengthens in local resource governance, on the other hand, presents resistance from civil society to take part in the legitimacy of power in the context of equitable distribution of resource management policies. The practice of community resistance is based on Sidney Tarrow's theory of collective challenge, common goals, solidarity and collective identity and maintaining the politics of resistance.